The need analysis of inculcating higher order thinking skills in design and technology - Mat Nor @ Ahmad Nor, Mohamad Nurul Azmi; Kamarudin, Nurzatulshima; Abdul Manaf, Umi Kalthom; Mohd Puad, Mohd. Hazwan (Global Science Press, 2018)
Design and Technology (RBT) subjects in the Primary School Standard Curriculum (KSSR) is introduced by the Ministry of Education to stimulate and create a critical, creative and innovative human capital. Thinking skills are emphasized and prioritized in RBT's teaching and learning to develop the imagination and creativity of students in order to compete globally parallel with the evolution worldwide. As an implementer of the established curriculum, the success of this aspiration depends on the teachers’ content knowledge and pedagogical skills. Therefore, the purpose of this study is to observe the level of content knowledge and pedagogical skills in RBT among teachers in primary schools. Furthermore, the results will be implemented in developing a Thinking Skills Training Module that emphasized on higher-order thinking skills (HOTS) in RBT. A total of 320 RBT teachers in the primary school of the Central Zone were involved in this study. The findings show that the teacher’s content knowledge and pedagogical skills rated as moderate level. This situation shows that teachers' knowledge in RBT’s content is still inadequate and they have not grasped the pedagogical skills to be integrated in higher order thinking skills (HOTS) of teaching and learning the RBT subjects in primary schools.